An initial fMRI study on neural correlates of prayer in members of Alcoholics Anonymous. (2nd January 2017) - Galanter, Marc; Josipovic, Zoran; Dermatis, Helen; Weber, Jochen; Millard, Mary Alice
ABSTRACT: Background : Many individuals with alcohol-use disorders who had experienced alcohol craving before joining Alcoholics Anonymous (AA) report little or no craving after becoming long-term members. Their use of AA prayers may contribute to this. Neural mechanisms underlying this process have not been delineated. Objective : To define experiential and neural correlates of diminished alcohol craving following AA prayers among members with long-term abstinence. Methods : Twenty AA members with long-term abstinence participated. Self-report measures and functional magnetic resonance imaging of differential neural response to alcohol-craving-inducing images were obtained in three conditions: after reading of AA prayers, after reading irrelevant news, and with passive viewing. Random-effects robust regressions were computed for the main effect (prayer > passive + news) and for estimating the correlations between the main effect and the self-report measures. Results : Compared to the other two conditions, the prayer condition was characterized by: less self-reported craving; increased activation in left-anterior middle frontal gyrus, left superior parietal lobule, bilateral precuneus, and bilateral posterior middle temporal gyrus. Craving following prayer was inversely correlated with activation in brain areas associated with self-referential processing and the default mode network, and with characteristics reflecting AA program involvement. Conclusion : AA members' prayer was associated with a relative reduction in self-reported craving and with concomitant engagement of neural mechanisms that reflect control of attention and emotion. These findings suggest neural processes underlying the apparent effectiveness of AA prayer.